In-situ analysis of continuous cooling precipitation in Al alloys by wide-angle X-ray scattering. Issue 1 (31st January 2020) - Rowolt, Christian; Fröck, Hannes; Milkereit, Benjamin; Reich, Michael; Kowalski, Wolfgang; Stark, Andreas; Keßler, Olaf
ABSTRACT: The aim of this work is to investigate quench induced precipitation during continuous cooling in aluminium wrought alloys EN AW-7150 and EN AW-6082 using in situ synchrotron wide-angle X-ray scattering (WAXS). While X-ray diffraction is usually an ex situ method, a variety of diffraction patterns were recorded during the cooling process, allowing in situ analysis of the precipitation process. The high beam energy of about 100 keV allows the beam to penetrate a bulk sample with a 4 mm diameter in a quenching dilatometer. Additionally, the high intensity of a synchrotron source enables sufficiently high time resolution for fast in situ cooling experiments. Reaction peaks could be detected and compared with results from differential scanning calorimetry (DSC) by this method. A methodology is presented in this paper to evaluate WAXS data in a way that is directly comparable to DSC-experiments. The results show a high correlation between both techniques, DSC and WAXS, and can significantly improve continuous cooling precipitation diagrams. GRAPHICAL ABSTRACT: uf0001